Assessment of educational environment using DREEM in a Pakistani medical college: a cross-sectional study - Akhlaq, Sana; Umara Yousuf; Uzma Aftab; Sadia Yaseen (Journal of the Pakistan Medical Association, 2026)
Objective: To evaluate the medical educational environment of an institution using integrated medical curriculum. Method: The cross-sectional study was conducted from September 1 to November 1, 2024, at Gujranwala Medical College, Gujranwala, Pakistan, and comprised medical students regardless of age, gender and academic year. Data was collected using the validated Dundee Ready Education Environment Measure questionnaire, covering five domains of the educational environment. Data was analysed using SPSS 28. Results: Of the 265 students, [n=88 (33.2%)] were males and [n=177 (66.8%)] were females. By year of study, [n=89 (33.6%)] were first year, [n=77 (29.1%)] second year, [n=32 (12.1%)] third year, [n=34 (12.8%)] fourth year, and [n=33 (12.5%)] final year. Regarding residence, [n=77 (29.1%)] were day scholars and [n=188 (70.9%)] were hostelites. The total mean DREEM score was 120.2 ± [22.2] (60%), reflecting moderately positive perceptions. Subscale analysis revealed highest scores in Students’ Perception of Learning (28.6±6.2) and lowest in Social Self-Perception (15.9±4.4). Significant differences across academic years were observed for all subscales (p<0.05). Regression analysis demonstrated that progression through academic years was significantly associated with declining scores in SPL, SASP, SPA, and SSSP (R²=0.06–0.15). No significant differences were noted by gender or residence status. Internal consistency was acceptable (Cronbach’s alpha=0.86; standardized=0.89). Conclusion: The evolving educational needs of students must be acknowledged through curricular adjustments to enhance student engagement, social support and professional competence. Key Words: Education, Medical, Learning environment, Students, Psychology, educational measurement, educational assessment.